Fairy tale interrupted [compact disc, unabridged] : a memoir of life, love, and loss - Terenzio, RoseMarie (Tantor Media, Inc., 2012)
To everyone else, John F. Kennedy, Jr. may have been American royalty, but to RoseMarie Terenzio he was an entitled nuisance, and she wasn't afraid to let him know it. RoseMarie was his personal assistant, his publicist, and one of his closest confidantes during the last five years of his life. In this, her first memoir, she bravely recounts her own Fairy Tale Interrupted, describing the unlikely friendship between a blue-collar girl from the Bronx and John F. Kennedy, Jr.